Development and validation of an LC-MS/MS method for determination of hydroxychloroquine, its two metabolites, and azithromycin in EDTA-treated human plasma - Sok, Vong (PLoS One, 2021)
BACKGROUND: Hydroxychloroquine (HCQ) and azithromycin (AZM) are antimalarial drugs recently reported to be active against severe acute respiratory syndrome coronavirus- 2 (SARS-CoV-2), which is causing the global COVID-19 pandemic. In an emergency response to the pandemic, we aimed to develop a quantitation method for HCQ, its metabolites desethylhydroxychloroquine (DHCQ) and bisdesethylchloroquine (BDCQ), and AZM in human plasma. METHODS: Liquid chromatography tandem mass spectrometry was used to develop the method. Samples (20 μL) are extracted by solid-phase extraction and injected onto the LC-MS/MS system equipped with a PFP column (2.0 × 50 mm, 3 μm). ESI(+) and MRM are used for detection. Ion pairs m/z 336.1→247.1 for HCQ, 308.1→179.1 for DHCQ, 264.1→179.1 for BDCQ, and 749.6→591.6 for AZM are selected for quantification. The ion pairs m/z 342.1→253.1, 314.1→181.1, 270.1→181.1, and 754.6→596.6 are selected for the corresponding deuterated internal standards (IS) HCQ-d(4), DHCQ-d(4), BDCQ-d(4), and AZM-d(5.) The less abundant IS ions from (37)Cl were used to overcome the interference from the analytes. RESULTS: Under optimized conditions, retention times are 0.78 min for BDCQ, 0.79 min for DHCQ, 0.92 min for HCQ and 1.87 min for AZM. Total run time is 3.5 min per sample. The calibration ranges are 2–1000 ng/mL for HCQ and AZM, 1–500 ng/mL for DHCQ and 0.5–250 ng/mL for BDCQ; samples above the range are validated for up to 10-fold dilution. Recoveries of the method ranged from 88.9–94.4% for HCQ, 88.6–92.9% for DHCQ, 88.7–90.9% for BDCQ, and 98.6%-102% for AZM. The IS normalized matrix effect were within (100±10) % for all 4 analytes. Blood samples are stable for at least 6 hr at room temperature. Plasma samples are stable for at least 66 hr at room temperature, 38 days at -70°C, and 4 freeze-thaw cycles. CONCLUSIONS: An LC-MS/MS method for simultaneous quantitation of HCQ, DHCQ, BDCQ, and AZM in human plasma was developed and validated for clinical studies requiring fast turnaround time and small samples volume.